Analisis Fundamental Makro Struktur Modal Kinerja Keungan Karakeristik Perusahaan Terhadap Nilai Perusahaan dengan GCG Sebagai Variabel Intervening pada Perusahaan Sektor Manufaktur yang Terdaftar di BEI Tahun 2018-2023 - Habiburrahman, Muhammad Riza Mahmud; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to analyze the effect of macro fundamentals, capital structure, financial performance, and company characteristics on firm value with Good Corporate Governance (GCG) as an intervening variable in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2023. The method used is secondary data analysis using the Smart-PLS version 4 program. The results showed that macro fundamentals, capital structure, financial performance, and company characteristics have a significant influence on firm value. In addition, GCG also has a significant influence on firm value. These results contribute to theory and practice in developing effective management strategies to increase firm value.